Empirical resilience and vulnerability model of regional group structure considering optimized macroseismic intensity measure. Issue 164 (January 2023) - Li, Si-Qi
Abstract: An optimized macroseismic intensity index, which integrates the traditional macroseismic intensity scale and the instrument intensity evaluation model, is proposed to evaluate regional buildings' empirical resilience and vulnerability. The traditional failure probability of the group structure is modified and improved. The parameters and probability indexes used to assess the resilience and vulnerability of group structure in urban and rural areas are innovatively proposed. The empirical group structure seismic loss data from the actual field investigation of the Jiuzhaigou earthquake in Sichuan Province, China, on August 8, 2017, were statistically analysed, the vulnerability of the sample data was assessed by using the optimized Chinese seismic intensity scale (OCSIS-20), European Macroseismic Scale (EMS-98) and the Modified Mercalli Intensity (MMI), and the assessment and comparison model of multidimensional modal resilience and probability index was established. To improve the rationality and accuracy of typical building resilience in the macrointensity quantification region, a new quantitative model of resilience and vulnerability based on optimizing the macrointensity index and updating the lognormal distribution is proposed, and the group structure resilience comparison models for typical macrointensity standard evaluation are established. The structural vulnerability database of the Jiuzhaigou earthquake is utilized to verify the rationality of the innovative model. Ultimately, field loss inspection and damage mechanism analysis are conducted based on the characteristics of regional structural seismic resilience and the actual vulnerability of the Jiuzhaigou earthquake. Highlights: The rapid resilience and vulnerability prediction and evaluation domain, plane, surface, and matrix based on quantity and failure index parameters are established. An innovative regional domain vulnerability and resilience assessment model is conducted. A new quantitative model of resilience and vulnerability based on optimizing the macrointensity index and updating the lognormal distribution is proposed.